Eternal message of Muhammad ; translated by Caesar.E. Farah - "Azzam, Abd-al-Rahman" (New York, 1964)
"Islam," writes a Christian historian, "is at once a culture and a religion, and in which the culture can hardly be conceived of as existing apart from religion. Consequently, if the Muslims lose their religion, they lose with in their culture and undergo a process of social dissolution. Moreever, the Arab nation (to which I belong), itself a creation of Islamic culture, would also cease to exist through the inevitable process of disintegration.
Keywords: Religion